Impact of eculizumab treatment on paroxysmal nocturnal hemoglobinuria: a treatment versus no‐treatment study. Issue 4 (June 2016) - Loschi, Michael; Porcher, Raphael; Barraco, Fiorenza; Terriou, Louis; Mohty, Mohamad; de Guibert, Sophie; Mahe, Beatrice; Lemal, Richard; Dumas, Pierre‐Yves; Etienne, Gabriel; Jardin, Fabrice; Royer, Bruno; et al.
Abstract : Intravascular hemolysis in Paroxysmal nocturnal hemoglobinuria (PNH) can effectively be controlled with eculizumab, a humanized monoclonal antibody that binds complement protein C5. We report here a retrospective comparison study between 123 patients treated with eculizumab in the recent period (>2005) and 191 historical controls (from the French registry). Overall survival (OS) at 6 years was 92% (95%CI, 87 to 98) in the eculizumab cohort versus 80% (95%CI 70 to 91) in historical controls diagnosed after 1985 (HR 0.38 [0.15 to 0.94], P = 0.037). There were significantly fewer thrombotic events (TEs) in the group of patients treated with eculizumab (4% [1–10]) as compared to the historical cohort (27% [20–34]). However, we found that TEs may still occur after the initiation of eculizumab treatment and that previous TEs still have a negative impact on survival. Evolutions to myelodysplastic syndrome or acute leukemia were similar in both cohorts. There was less evolution to aplastic anemia in the treatment group. In multivariate analysis, absence of a previous TE and treatment with eculizumab were associated with a better OS. Treatment with eculizumab improves overall survival in classic PNH patients without increasing the risk of clonal evolution. Am. J. Hematol. 91:366–370, 2016. © 2016 Wiley Periodicals, Inc.